Penerapan Atribut Produk Keterampilan Mendesain Kemasan Dalam Pemasaran Beras - Depy Muhamad Pauzy; Dudu Risana; Arif Arif; Gian Riksa Wibawa (Jurdimas (Jurnal Pengabdian Kepada Masyarakat) Royal, 2023)
Abstract: The problem that occurs in rice producers is the lack of knowledge about the importance of branding, and the sales system is still conventional. The purpose of the community service program activities through the application of appropriate technology (PTTG) is to help rice producers in terms of developing their business so that they can develop more and increase their income. The effective steps that have been carried out by the community service team are starting with analyzing the situation in the field directly, then the results are used as a reference for community service. The method used is the application of appropriate technology (PTTG) in which the procedures are carried out through direct practice. Regarding this method, several steps are taken, namely carrying out initial observations at the location, then carrying out the preparation of activity plans, outreach and implementation of activities, and evaluation during the activity. The results obtained from this service are 1) There is an increase in knowledge related to the packaging design procedures for tjiawi ramos rice products 2) There is an increase related to product attributes that have been made 3) There is an increase in knowledge related to good branding procedures for rice and ramos businesses.            Keywords: Packaging Design; PKM; Setra Ramos Tjiawi  Abstrak:  Permasalahan yang terjadinya pada produsen beras adalah rendahnya pengetahuan mengenai pentingnya branding, dan sistem penjualan yang masih konvensial. Tujuan kegiatan program pengabdian kepada masyarakat melalui penerapam teknologi tepat guna (PTTG) ini ialah untuk membantu produsen beras dalam hal pengembangan usahanya agar lebih berkembang dan adanya peningkatan pendapatan. Langkah efektif yang sudah dijalankan oleh tim pengabdian ialah diawali dengan menganalisis situasi dilapangan secara langsung kemudian hasilnya dijadikan sebagai acuan pengabdian. Metode yang digunakan ialah penerapan teknologi tepat guna (PTTG) yang tata caranya dilakukan melalui praktik secara langsung. Terkait metode ini maka beberapa langkah yang dilakukan ialah melakukan obervasi awal ke lokasi, kemudian melakukan penyusunan rencana kegiatan, sosialisasi dan pelaksanaan kegiatan, dan evaluasi selama kegiatan berlangsung . Hasil yang diperoleh dari adanya pengabdian ini ialah 1) Adanya peningkatan pengetahuan terkait tata cara desain kemasan produk beras  tjiawi ramos 2) Adanya peningkatan terkait atribut produk yang sudah dibuat 3) Adanya peningkatan pengetahuan terkait tatacara branding yang baik bagi usaha beras serta ramos. Kata kunci: Desain Kemasan; PKM; Setra Ramos Tjiawi